SCIENTIFIC, THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR THE PREVENTION OF DOMESTIC VIOLENCE AGAINST WOMEN AND ADOLESCENT GIRLS (Journal of actual problems of jurisprudence, 2025)
The study is devoted to a comprehensive scientific and theoretical understanding of domestic violence against women and adolescent girls as a multidimensional socio-legal phenomenon that has a destructive impact on the institution of the family, social relations, and sustainable development processes. The article examines the essential characteristics of this phenomenon, its causes and consequences, and reveals contemporary approaches to constructing an effective prevention system.The purpose of the research is to develop an integral concept for the prevention of domestic violence based on the synthesis of legal, sociological, psychological, and humanitarian knowledge. The scientific novelty of the work lies in the substantiation of an integrative model of prevention combining key theoretical approaches — gender-based, socio-ecological, victimological, intersectional, and human rights — which make it possible to view violence as a consequence of structural inequality and institutional dysfunctions.The methodological framework of the study is founded on the principles of interdisciplinarity, evidence-based analysis, and comparative legal methodology. This approach has made it possible to identify the interconnection between social factors, cultural patterns, and the effectiveness of legal protection mechanisms.As a result of the analysis, the main directions for improving the prevention system have been identified, including legal regulation, educational initiatives, social support, and multi-level intervention mechanisms. Special attention is paid to adapting international standards and World Health Organization recommendations to Kazakhstan’s national context and developing a three-tier structure of prevention.The scientific and practical significance of the research lies in the development of theoretical and methodological foundations for state policy aimed at reducing gender-based violence, strengthening legal safeguards, and fostering a culture of non-violent social interaction.Keywords: domestic violence; gender equality; prevention of violence; protection of the rights of women and adolescent girls; state policy.